An Analysis on Vocabulary Learning Strategies (VLS) Used by Junior High School Students - Urai Salam; Elpit Ade Fitrianti; Eusabinus Bunau (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This research identifies the vocabulary learning strategies used by junior high school students. The participants were 103 students from the ninth grade of SMP Negeri 2 Semparuk in the academic year 2020/2021. The data were derived from an open-ended questionnaire which consisted of 5 questions using qualitative analysis, and a close-ended questionnaire consisting of 20 items using descriptive statistics. There were four strategies covered in the questionnaire: metacognitive, cognitive, memory, and activation strategies. Based on the data collected, some students shared their experiences of learning vocabulary daily. They only focused on finding the strategies that will support their learning of English vocabulary by translating, memorizing, taking notes, and highlighting the words that they are going to learn for the next day. They also practiced making sentences using the words they have found. The result also showed that the most frequently used strategies by the ninth-grade students of SMP Negeri 2 Semparuk are activation strategies (M=2.52), then respectively followed by cognitive strategies (M=2.16), memory strategies (M=2.14), and metacognitive strategies (M=2.05).